A High Preoperative Platelet-Lymphocyte Ratio Is a Negative Predictor of Survival After Liver Resection for Hepatitis B Virus-Related Hepatocellular Carcinoma: A Retrospective Study - Yang, Yun; Wang, Meng-chao; Tian, Tao; Huang, Jian; Yuan, Sheng-xian; Liu, Lei; Zhu, Peng; Gu, Fang-ming; Fu, Si-yuan; Jiang, Bei-ge; Liu, Fu-chen; Pan, Ze-ya; et al. (Frontiers in Oncology, 2020)
Objective: To evaluate the significance of preoperative blood platelet to lymphocyte ratio (PLR) in patients with hepatitis B virus (HBV)-related hepatocellular carcinoma (HCC) after hepatectomy and to examine the connection with CD8+ lymph cell infiltration. Methods: Between 2009 and 2014, consecutive HCC patients with hepatectomy were enrolled into this retrospective study. The clinicopathological characteristics were analyzed to identify predictors of recurrence-free and overall patient survival rate after liver resection. The samples of all patients were under Tissue Microarray (TMA) construction and immunohistochemical staining for CD8+.The association of the number of CD8+T-cells in the cancer nests and peritumoral stroma with PLR level was analyzed. Results: A total of 1174 HBV-related HCC patients who received a liver resection without any peri-operative adjuvant therapy were enrolled into this retrospective study. Univariate and multivariate analysis using the Cox proportional hazards model showed PLR was an independent factor affecting recurrence and overall survivals. The optimal cutoff of PLR using the receiver operating characteristic curve was 150. There were 236 patients (20.1%) who had a PLR of 150 or more. The 5-year survival rate after liver resection was 71.8% in patients with a PLR of less than 150 and it was 57.2% in those with a PLR of 150 or more (P < 0.001). The 5-year tumor recurrence and overall survival rates in liver cancer stage A patients at Barcelona Clinic with different PLR group were also significantly different (P = 0.007 for recurrence and P = 0.001 for overall survival). Similar results were also observed in Barcelona Clinic liver cancer stage B patients (P < 0.001 for recurrence and P = 0.033 for overall survival). To determine the association between PLR and the severity of liver inflammation, an immuno-histological examination using CD8+ staining was performed on the liver specimens of 1174 patients. The number of CD8+T-cells was significantly higher in the peritumoral tissue in the high PLR (≥ 150) group than in the low PLR (< 150) group (P = 0.001). Conclusions: PLR was an independent predictor of HCC patients. A high PLR was associated with an accumulation of CD8+ T-cells in the peritumoral stroma.